Effectiveness of CONUT and NRI as nutritional risk screening tools in peritoneal dialysis: a multicenter study - Qiu, Wenlong; Chu, Rui; Ma, Yaqi; Xue, Jiaxin; Xu, Qingdong; Wen, Yueqiang; Zhan, Xiaojiang; Peng, Fenfen; Wang, Xiaoyang; Wu, Juan; Su, Ning; Feng, Xiaoran; et al. (Frontiers in Nutrition, 2025)
BackgroundNutritional risk is a significant concern for patients undergoing peritoneal dialysis (PD), adversely affecting their quality of life and increasing the risk of infections and complications. Effective screening tools are needed to identify high-risk patients for targeted interventions. This study investigates whether different nutritional assessment methods, like the Controlling Nutritional Status (CONUT) score and Nutritional Risk Index (NRI), correlate with patient prognosis, highlighting the importance of selecting appropriate screening tools to improve clinical outcomes in PD patients.MethodsThis multicenter retrospective cohort study initially collected data from 2,427 patients across 10 centers, but ultimately included a cohort of 2,105 PD patients to evaluate the prevalence of malnutrition assessed using both the CONUT and NRI and its independent effects on all-cause mortality. Statistical analyses included log-rank tests, Cox regression models and the receiver operating characteristic curves to evaluate the association between nutritional risk and mortality.ResultsOur findings revealed that 76.58% of patients were classified as having nutritional risk according to the CONUT score, while 79.10% by the NRI. Patients with nutritional risk exhibited a significantly higher all-cause mortality rate (log-rank test, p < 0.001). Cox regression analysis demonstrated that severe nutritional risk was an independent predictor of all-cause mortality, with adjusted hazard ratios of 2.55 (95% CI, 1.34–4.85; p = 0.007) for the CONUT score and 2.64 (95% CI, 1.74–4.03; p < 0.001) for the NRI. Kaplan–Meier survival curves highlighted the correlation between nutritional risk and survival.ConclusionCONUT and NRI are effective for initial nutritional risk screening in PD patients, enabling clinicians to identify risk individuals who should undergo diagnostic assessments for a more comprehensive nutritional evaluation. Their simplicity and ease of implementation support integration into routine practice, making it feasible for healthcare providers to conduct regular screenings. Future studies should validate dynamic monitoring approaches.